Brongniartia montalvoana (Fabaceae: Faboideae), una especie nueva de la Cuenca del Río Balsas - Dorado, Oscar; Arias, Dulce M. (Instituto de Ecología, A.C., 1992)
A new species of Fabaceae, Brongniartia montalvoana, from the Rio Balsas Basin is described and illustrated. Its affinities with B. mortonii McVaugh as well as their distinguishing morphological characteristics are discussed and habitat data are presented.